Nineteenth-Century Art Worldwide : NCAW ; a Journal of Nineteenth Century Visual Culture. (College Park-Maryland : Association of Historians of nineteenth century Art, 2002)
Founded in 2002, Nineteenth-Century Art Worldwide (NCAW) is a scholarly, refereed, open-access journal devoted to the study of nineteenth-century art and visual culture across the globe. Open to various historical and theoretical approaches, the editors welcome contributions that reach across national boundaries and illuminate intercultural contact zones in the broadest sense of that term. The chronological scope of the journal is the “long” nineteenth century, stretching from the American and French Revolutions at one end to the outbreak of World War I at the other, a period coinciding with the apex of European colonialism and the first phase of (unfettered) industrial capitalism.(https://www.19thc-artworldwide.org/vision-and-history)
Online: https://www.19thc-artworldwide.org
Engels
Tijdschriften
Keywords: 19de eeuw